Hydrogen motions in defective graphene: the role of surface defects. Issue 36 (26th August 2016) - Cavallari, Chiara; Pontiroli, Daniele; Jiménez-Ruiz, Mónica; Johnson, Mark; Aramini, Matteo; Gaboardi, Mattia; Parker, Stewart F.; Riccó, Mauro; Rols, Stéphane
Abstract : Understanding the mobility of H at the surface of carbon nanostructures is one of the essential ingredients for a deep comprehension of the catalytic formation of H2 in interstellar clouds. Abstract : Understanding the mobility of H at the surface of carbon nanostructures is one of the essential ingredients for a deep comprehension of the catalytic formation of H2 in interstellar clouds. In this paper, we combine neutron vibrational spectroscopy with DFT molecular dynamics simulations to study the local environment of H structures chemisorbed at the surface of disordered graphene sheets. At 5 K, the ground state is composed of large clusters of hydrogen chemisorbed at sp 2 carbon sites, on the edges and in voids of the graphene sheets. At temperatures of ∼300 K, a high degree of dispersion of the clusters is observed, involving the breaking and reforming of covalent bonds which, at low temperatures, is mediated by incoherent tunnelling of hydrogen.